Efeito da perda da cobertura florestal na atividade turística da Amazônia Central - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
One of the issues of great concern is the loss of forest cover in areas of tourism development in some regions of the Central Amazon, specifically in the study area, which is promoted intensively by human pressures such as agriculture for cutting and burning, livestock, opening of secondary roads (branches), settlement projects and the expansion of President Figueiredo´s urban area. The conservation of forests is vital and essential for the provision of environmental services not only for the maintenance of tourism activity in the region but also for the regulation of natural cycles, biodiversity conservation, water quality, soil, climate, among others, providing benefits (direct and indirect) to local human populations and the whole world. This study aimed to analyze the effect of the loss of forest cover and its influence on tourist activity in the Central Amazon, specifically in Presidente Figueiredo. The results of this study provide relevant information on the spatial-temporal prediction of deforestation, analysis of tourist carrying capacity and the forest degradation state (in terms of a degraded forest) in the trails of tourist attractions, and application of an economic valuation method on hypothetical scenarios for forest conservation. In Chapter 1, the land cover datas (PRODES/INPE), static/dynamic variables, evidence weights, agrarian and accessible forest surface calculations were used in the AGROECO model to simulate the spatiotemporal distribution of deforestation until 2050. It was determined that there would be a 22,38% increase in deforestation from 2017 to 2050 in the study area, allocated along the margins of highways (BR-174 and AM-240), exclusively with spatial distribution on secondary roads near the Presidente Figueiredo´s city and at the northern sector of the study area, in addition to its minor repercussion on the forest coverage areas of the most tourist attractions. In Chapter 2 presents quantitative results of the tourist carrying capacity of fifteen (15) tourist attractions applied to trails, determined by Cifuentes et al. (1999) method, which establishes three levels: physical, real and effective, with the purpose of estimating the users flow during the visit, and verify the forest degradation state in these locations. It is essential to highlight that the attractions of "Neblina", "Complejo do Iracema Falls" and "Cachoeira da Onça" were that they showed a maximum recommended level of users per day. In Chapter 3, 226 people were interviewed to estimate the willingness to pay (WTP, n = 206) of users and the willingness to accept (WTA, n = 20) from those interviewed (public and private employees and landowners) for forest conservation, using the contingent valuation method. It was observed that 71,4% of users would be willing to pay an estimated value of R$ 11,72 day-1visit-1. In comparison, 100% of interviewees would be willing to accept an amount of R$ 105,22 ha-1year-1, as payment and compensation for the conservation of the forests. Therefore, these results demonstrated that the tourist attractions inhibit the advance of deforestation, in addition to be considered as a proposal to assist in decision making by the actors involved in environmental governance for an adequate tourism management in the region.

Uno de los problemas que más preocupa es la pérdida de la cubierta forestal en las zonas de desarrollo turístico de algunas regiones de la Amazonía Central, concretamente en el área de estudio, que se ve impulsada intensamente por presiones humanas como la agricultura de roza y quema, la ganadería, la apertura de carreteras secundarias, los proyectos de asentamiento y la expansión del área urbana de Presidente Figueiredo. La conservación de los bosques es muy importante y esencial para la prestación de servicios ambientales no sólo para el mantenimiento de la actividad turística en la región, sino también para la regulación de los ciclos naturales, el mantenimiento de la biodiversidad, la calidad del agua, el suelo, el clima, entre otros, proporcionando beneficios (directos e indirectos) a las poblaciones humanas locales y al mundo entero. Este estudio tuvo como objetivo analizar el efecto de la pérdida de la cubierta forestal y su influencia en la actividad turística de la Amazonía Central, específicamente en Presidente Figueiredo. Los resultados de este estudio proporcionan información pertinente sobre la predicción espacio-temporal de la deforestación, el análisis de la capacidad de carga y el estado de degradación de los bosques en los senderos de los atractivos turísticos, y la aplicación de un método de valoración económica para escenarios hipotéticos de conservación de los bosques. En el capítulo 1, datos de cobertura de la tierra del PRODES/INPE, variables estáticas/dinámicas, pesos de evidencia y los cálculos de la cubierta forestal agraria y accesible, se utilizaron en el modelo AGROECO para simular la distribución espacio-temporal de la deforestación hasta 2050. Se determinó que se produciría un aumento del 22,38% de la deforestación de 2017 a 2050 en el área de estudio, distribuido a lo largo de los márgenes de las carreteras pavimentadas (BR-174 y AM-240), exclusivamente con distribución espacial en las carreteras secundarias cercanas a la ciudad de Presidente Figueiredo y en el sector Norte del área de estudio, además de su menor repercusión en las zonas de cubierta forestal de la mayoría de los atractivos turísticos. En el capítulo 2 se presentan resultados cuantitativos de la capacidad de carga turística de quince atractivos aplicados a senderos, determinados por el método de Cifuentes et al. (1999), que establece tres niveles: físico, real y efectivo, con el fin de estimar el flujo de usuarios durante la visita y verificar el estado de degradación forestal en estos lugares. Cabe señalar que los atractivos de "Neblina", "Complejo do Iracema Falls" y "Cachoeira da Onça" fueron que mostraron un nivel máximo recomendado de usuarios por día. En el capítulo 3, se entrevistó a 226 personas para estimar la disposición a pagar (DAP, n = 206) de los usuarios y la disposición a aceptar (DAA, n = 20) de los entrevistados (empleados públicos y privados, y propietarios de terreno) para la conservación de los bosques, utilizando el método de valoración de contingencia. Se observó que el 71,4% de los usuarios estarían dispuestos a pagar un valor estimado de R$ 11,72 día-1visita-1, mientras que el 100% de los entrevistados estarían dispuestos a aceptar un valor de R$ 105,22 ha-1año-1, como pago y compensación por la conservación de los bosques. Por lo tanto, estos resultados demostraron que los atractivos turísticos inhiben el avance de la deforestación, además de ser considerados como una propuesta para ayudar en la toma de decisiones por parte de los actores involucrados en la gobernanza ambiental para una adecuada gestión del turismo en la región.
Efecto de la pérdida de la cobertura forestal en la actividad turística de la Amazonía Central
Effect of loss of forest cover on tourist activity in Central Amazonia
Keywords: Desmatamento; Modelagem espacial; Presidente Figueiredo (Amazonas); Turismo amazônico; Spatial modelling; CIÊNCIAS AGRÁRIAS; Amazônia; Desmatamento; Modelagem espacial; Capacidade de carga turística; Valoração econômica de contingência; Presidente Figueiredo